1992
DOI: 10.1148/radiology.183.1.1312735
|View full text |Cite
|
Sign up to set email alerts
|

Mucin-producing pancreatic tumor: CT findings and histopathologic correlation.

Abstract: Twenty patients with mucin-producing pancreatic tumor and 60 with other pancreatic diseases underwent computed tomography (CT) to establish the CT characteristics of mucin-producing pancreatic tumor. Scans were obtained with thin sections by administering a large volume of contrast material (200 mL). Mucin-producing pancreatic tumors were divided into three subgroups, and the CT characteristics were as follows: Main duct type tumors consisted of a cystic mass in or communicating with the dilated main pancreati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
36
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(42 citation statements)
references
References 0 publications
6
36
0
Order By: Relevance
“…However, most of these reports are based on a small number of patients and univariate analysis, and, therefore, conclusions of a high malignancy rate for the main duct type should be treated as tentative. [22][23][24] Another pitfall in this classification is the discrepancy between the dilated ductal segments and the actual presence of tumor cells. 21 Kamisawa et al 25 reported two autopsy cases of benign IPMT of the main pancreatic duct type in patients who were followed up for approximately 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these reports are based on a small number of patients and univariate analysis, and, therefore, conclusions of a high malignancy rate for the main duct type should be treated as tentative. [22][23][24] Another pitfall in this classification is the discrepancy between the dilated ductal segments and the actual presence of tumor cells. 21 Kamisawa et al 25 reported two autopsy cases of benign IPMT of the main pancreatic duct type in patients who were followed up for approximately 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…Mural nodule and papillary projections were confirmed on resected specimen. On CT scans, an IV bolus injection of con trast medium using contiguously thin-sec tion slices (5 mm) is recommended to fully visualize cystic components of mucin-pro ducing pancreatic tumors [4]. MRCP needs no injection of contrast material and can pro vide the precise projection images of the cystic lesions.…”
Section: Bercp Image Shows Simultaneous Opacification Ofclusterlike mentioning
confidence: 99%
“…On CT and sonography, the tumor appears as clustered small cystsor asa cystic lesionwith a lobulated or irregular marginandsparse septa, characteris tics that are often associated with dilatation of the pancreatic duct near the lesion [4,5].…”
mentioning
confidence: 99%
“…Microcystic adenomas are the most common variant. As a rule they are benign and are comprised of a central scar with surrounding small cysts [26]. The scar can contain calcifications.…”
Section: Serous Cystic Neoplasia (Scn)mentioning
confidence: 99%